Enhancing students' English short story writing skills containing religious moderation values: A mentorship program - Azizah, Siti; Rahmawati, Fithriyah; Febrianingrum, Lasmi; Rabi'ah; Sufyan, Akhmad Farid Mawardi (PERDIKAN (Journal of Community Engagement), 2024)
Religious moderation is an essential concept that should be taught and practiced by the students in Islamic senior high schools (Madrasah Aliyah), particularly in the context of an increasingly diverse society. Religious moderation emphasizes on balance, moderation, tolerance and respect for differences, both in terms of beliefs and religious practices. This community service program aimed to enhance students’ English short story writing skills which is integrated with religious moderation values. The mentorship program was conducted at MAN 2 Pamekasan and enrolled 25 students as participants. The program was carried out by applying Asset Based Community Development (ABCD) as a community service approach which consists of discovery, dream, define, design, and destiny. The activities were internalizing the religious moderation values to the students and practicing to write English short stories guided by facilitators. The result of the present community service shows that the students are gaining a better understanding of religious moderation, demonstrating improved writing skills, and being able to reflect the values of religious moderation in their short stories. The result suggested that combining creative writing with religious moderation value-based education can foster both linguistics competence and character development. Therefore, it contributes to a more harmonious school environment.[Moderasi beragama merupakan konsep penting yang harus diajarkan dan dipraktikkan oleh siswa di Madrasah Aliyah, terutama dalam konteks masyarakat yang semakin beragam. Moderasi beragama menekankan keseimbangan, toleransi, dan penghormatan terhadap perbedaan, baik dalam hal keyakinan maupun praktik keagamaan. Program pengabdian masyarakat ini bertujuan untuk meningkatkan keterampilan menulis cerpen berbahasa Inggris siswa yang terintegrasi dengan nilai-nilai moderasi beragama. Program pendampingan ini dilaksanakan di MAN 2 Pamekasan dengan melibatkan 25 siswa sebagai peserta. Program ini menggunakan pendekatan Asset Based Community Development (ABCD) dalam pengabdian masyarakat yang terdiri dari tahap discovery, dream, define, design, dan destiny. Kegiatan yang dilakukan yaitu internalisasi nilai-nilai moderasi beragama kepada siswa serta pelatihan menulis cerpen berbahasa Inggris yang dibimbing oleh para fasilitator sekaligus pengabdi. Hasil dari pengabdian ini menunjukkan bahwa para siswa memperoleh pemahaman yang lebih baik tentang moderasi beragama, menunjukkan peningkatan kemampuan menulis, dan mampu merefleksikan nilai-nilai moderasi beragama dalam cerpen mereka. Hasil pengabdian Masyarakat ini merekomendasikan bahwa menggabungkan penulisan kreatif dengan pendidikan berbasis nilai moderasi beragama dapat meningkatkan kompetensi linguistik sekaligus pengembangan karakter. Dengan demikian, hal ini berkontribusi pada terciptanya lingkungan sekolah yang lebih harmonis.]